(untitled) (Cardiovascular Journal, 2023)
One of the rare cardiac anomaly is Sinus of Valsalva aneurysm (SVA) that can rupture spontaneously into other cardiac chambers or the pericardial space.1 Here, we report a rare case of a right coronary sinus of Valsalva aneurysm with rupture into the Left ventricular outflow tract (LVOT). Cardiovasc j 2023; 15(2): 182-184